Descriptions and revised key to the eggcases of the skates (Rajiformes: Rajidae) and catsharks (Carcharhiniformes: Scyliorhinidae) of the British Isles - Gordon, Cat A.; Hood, Ali R.; Ellis, Jim R. (Zootaxa, 2016)
Updated descriptions and measurements for the eggcases of 10 rajiform and three scyliorhinid species occurring in the shelf seas around the British Isles are given, based on museum material, specimens collected during the ‘Great Eggcase Hunt’ (a Shark Trust recording project), and specimens obtained from fishery surveys. Quantitative data are given for Amblyraja radiata (n = 94), Dipturus batis (n = 24), D. cf. intermedia (n = 33), Leucoraja naevus (n = 94), Raja brachyura (n = 53), R. clavata (n = 52), R. microocellata (n = 57), R. montagui (n = 52), R. undulata (n = 52), Rostroraja alba (n = 5), Galeus melastomus (n = 7), Scyliorhinus canicula (n = 52) and S. stellaris (n = 58). An updated key for the identification of elasmobranch eggcases is provided, incorporating recent changes in skate taxonomy.